2020
DOI: 10.1094/pdis-09-19-1948-re
|View full text |Cite
|
Sign up to set email alerts
|

Management of Fire Blight Using Pre-bloom Application of Prohexadione-Calcium

Abstract: Fire blight, a bacterial disease of rosaceous plants caused by Erwinia amylovora, is one of the most important diseases affecting commercial apple production worldwide. Antibiotics, applied at bloom to protect against blossom infection, are the most effective means of management but raise concern due to the potential for antibiotic resistance in both the pathogen population and nontarget organisms. In addition, most fire blight outbreaks in New York State often emerge in late June to July as shoot blight, call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…programs 3 (one PCA high) and 4 (two PCA high) on shoot blight severity in the present study suggest that the high PCA rates require less than 10 to 14 days to take effect after application, which is contrary to this timeline currently viewed as required for PCA's mode of action to express (Wallis and Cox 2020). This implies that the immediately accessible (i.e., absorbed) dose of PCA that reaches inside the apple shoots plays a key role in achieving the desired host changes (McGrath et al 2009), triggering quicker interruption of E. amylovora invasion through shoots.…”
contrasting
confidence: 91%
See 2 more Smart Citations
“…programs 3 (one PCA high) and 4 (two PCA high) on shoot blight severity in the present study suggest that the high PCA rates require less than 10 to 14 days to take effect after application, which is contrary to this timeline currently viewed as required for PCA's mode of action to express (Wallis and Cox 2020). This implies that the immediately accessible (i.e., absorbed) dose of PCA that reaches inside the apple shoots plays a key role in achieving the desired host changes (McGrath et al 2009), triggering quicker interruption of E. amylovora invasion through shoots.…”
contrasting
confidence: 91%
“…Prohexadione-calcium (PCA) is a valuable PGR that activates structural resistance in vegetative apple tissues to E. amylovora (Sundin 2014) (Apogee, BASF Corporation; Kudos 27.5 WDG; Fine Americas). PCA inhibits gibberellin biosynthesis, which reduces longitudinal apple shoot growth and increases the thickness of cell walls in cortical parenchyma, thus preventing invasion of shoot tissues by E. amylovora and reducing shoot susceptibility to fire blight (Evans et al 1999;McGrath et al 2009;Ramirez et al 2005;Wallis and Cox 2020). Preventive spray applications of PCA are recommended in commercial apple orchards starting at the 2.5-to 5-cm shoot growth stage and continuing at 1-to 4-week intervals after the first application because they reduce shoot blight incidence as much as 83% and shoot blight severity as much as 86% (Momol et al 1998;Yoder et al 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to fungal plant diseases, to control a bacterial plant disease a combination of multiple control approaches and methods is necessary (Agrios, 2005). For example, control of fire blight usually involves planting resistant cultivars, spray application of copper bactericides, antibiotics, biological materials, activators of Systemic Acquire Resistance (SAR), shoot growth retardants, and mechanical removal of infected tree parts by pruning or whole tree removal (Johnson and Temple, 2013;Johnson and Temple, 2015;Wallis and Cox, 2019;Acímovićet al, 2021;Philion and Joubert, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many reports have indicated that ProCa can reduce the intensity of many diseases, such as fire blight in pears, scab in apples, and gray molds in grapes (BAZZI et al, 2003;McGRATH et al, 2009;WALLIS & COX, 2020). McGrath et al (2009), suggested that ProCa triggers the production of flavanoids, not normally reported in rosaceous species, that provide antimicrobial activity against E. amylovora, and this activity is the primary mechanism of fire blight control by ProCa.…”
Section: Introductionmentioning
confidence: 99%